Effect of IBA hormone and mixture composition on the rooting of hardwood Cuttings of Lycium barbarum L. (Damascus University Journal of agriculture sciences, 2022)
The research was carried out in the nursery of the Faculty of Agriculture - Damascus University in 2019, the aim of research is to study the effect of each different concentrations of IBA (0, 1000, 2000 ppm) and the composition of the seedling mixture { soil + fermented municipal manure + sand 1: 1: 1 (A), soil + Fermented sewage sludge + sand 1: 1: 1 (B), soil + fermented municipal manure + fermented sewage sludge + sand 1: 1: 1: 1 (C) } on the rooting of hard wood cuttings of Lycium barbarum L. and its growth indicators. The cuttings were planted in polyethylene bags of 12 cm diameter, with three replications for each treatment, and seven bags for each replication. The average length of shoot, average length and number of roots) were studied. Furthermore, by using analysis of variance and Genstat 12th program, the statistical analysis of indicators values was performed, and the L.S.D0.05 was calculated. The results showed that the treatment with concentrations of 1000 and 2000 ppm significantly exceeded the control treatment with the values of 79.36% and 65.08% respectively. While the mixture B significantly exceeded the mixture A with the values of 77.78% and 69.84% respectively. As for the average root length, the treatment with concentrations of 1000 and 2000 ppm significantly exceeded the control treatment with the values of 47.85, 50.09 and 42.31 cm respectively, and the mixture C significantly exceeded the mixture A with the values of 50.28 cm and 43.10 cm respectively. Regarding the average number of roots, the treatment 2000 ppm significantly exceeded (15.42 root/cutting) over both the treatment 1000 (13.62 ppm root/cutting) and the control (9.40 root/cutting), the mixture C (14.52 root/cutting) significantly exceeded each of the two mixes A (10.94 root/cutting) and B (12.98 root/cutting). Finally, Regarding the average root length, the treatment 1000 and 2000 ppm significantly exceeded the control treatment with the values of 10.90, 11.75 and 9.69 cm respectively. the mixture C significantly exceeded each of the mixtures A and B with the values of 12.63, 8.42 and 11.28 cm respectively.
Keywords: Lycium barbarum L.; hardwood cuttings; mixture composition; indole butyric acid (IBA)